Conduction electron spin resonance in Mg1-xAlxB2 - V. Likodimos; Koutandos, S.; Pissas, M.; Papavassiliou, G.; Prassides, K. (Europhysics Letters, 2003)
Conduction electron spin resonance is employed to study the interplay of the electronic and structural properties in the normal state of Mg1-xAlxB2 alloys as a function of Al-doping for 0 ≤ x ≤ 1. The x-dependence of the spin susceptibility reveals considerable reduction of the total density of states N(EF) with increasing Al concentration, complying with theoretical predictions for a predominant filling effect of the hole σ bands by electron doping. The CESR linewidth exhibits significant broadening, especially prominent in the high-Al-content region, indicative of the presence of enhanced structural disorder, consistent with the presence of compositional fluctuations.